Concepts, Compounds and the Alternatives of Antibacterials - Bobbarala, Varaprasad (IntechOpen, 2015)
This edition is intended to provide better understanding of antibacterial drugs and their mechanism, the role of a few metal drug complexes as antibacterials, cross-checking of a few compounds and biomaterials against drug-resistant bacterial strains as well as a few alternative approaches using medicinal plant based formulations in the control of antibiotic-resistant bacteria. The information in this book provides clues for upcoming trends in treating antibiotic resistance problems with which one can explore new approaches in the treatment of common infections with drug-resistant strains.